2001
DOI: 10.1103/physrevb.63.205203
|View full text |Cite
|
Sign up to set email alerts
|

Excitation dynamics in single molecular crystals of α-hexathiophene from femtoseconds to milliseconds

Abstract: We identify odd-and even-parity states and measure transient photomodulation spectra of Frenkel excitons in ␣-hexathiophene single crystals. The lowest Frenkel excitons are characterized by a stimulated emission band at ϳ2 eV and an absorption band at 1.3 eV. Intramolecular internal conversion governs transitions from upper excited states to the lowest exciton and occurs in 200 fs. We observe exciton trapping on the nanosecond time scale; as a result, the millisecond photomodulation spectrum is dominated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
7
33
1
Order By: Relevance
“…This is in sharp contrast to experimental studies in which such relaxation processes are observed within a time interval of less than 0:5 ps after excitation [3,8]. This is not an artifact of the choice of initial condition, since we always observe the internal conversion process to take place over several hundreds of femtoseconds.…”
Section: Article In Presscontrasting
confidence: 76%
See 4 more Smart Citations
“…This is in sharp contrast to experimental studies in which such relaxation processes are observed within a time interval of less than 0:5 ps after excitation [3,8]. This is not an artifact of the choice of initial condition, since we always observe the internal conversion process to take place over several hundreds of femtoseconds.…”
Section: Article In Presscontrasting
confidence: 76%
“…It is therefore difficult to estimate the exact duration of the relaxation of the electronic system. From, e.g., transient photomodulation spectroscopic studies of photoexcitation dynamics in both ultra pure tetracene crystals [21] and ahexathiophene crystals [3] intramolecular internal conversion is found to take less than 200 fs. As a reference, we note that it takes roughly 1:1 ps for the system to go from the state of occupation when n 116 first drops below 0.50 at t$0:5 ps to that when n 111 rises above 0.50 at t$1:6 ps.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations